Molecular and morphological circumscription of Brachythecium coruscum as a separate taxon from Brachythecium albicans (Brachytheciaceae, Bryophyta) - Draper, Isabel; Mazimpaka, Vicente; Hedenäs, Lars (Phytotaxa, 2014)
Nuclear ITS, and chloroplast rpl16 and trnG sequences, together with morphological data, were used to circumscribe some problematic taxa within the complex around the pleurocarpous moss Brachythecium albicans. Brachythecium coruscum is consistently different from B. albicans, and its description is here amended. On the contrary, segregation of Brachythecium dumetorum from B. albicans is unsupported both according to molecular and morphological data, and the two taxa are therefore considered to be synonyms.